STUDI POTENSI LANSKAP BERSEJARAH UNTUK PENGEMBANGAN WISATA SEJARAH DI KOTA BENGKULU - Rika Anggraini; Nurhayati HS Arifin (Jurnal Lanskap Indonesia, 2011)
The objectives of this study were to invent and identify the exsistance of historic landscape in Bengkulu City, to analise and describehistoric landscape which is potential to develop and conserve and also to give some approachments of conservation and empowerment of historic landscape in Bengkulu City for historic tourism development. The method of the study was the surveymethod, including literature review, site observation, questionaire and interview for collecting data. The data were analised to describe the existence and the condition of historic landscapes, and to offer an alternative of historical tourism development.The result showed that Bengkulu City has long periodof history, which left historic landscape and cultural herritage as the physical evidences. The history started from kingdom period with high community welfare and invited the colonialism to Bengkulu. The City still has nationally important role in the early of the independence period of Indonesian Republic. In this  study, 18 cultural reserve and historic landscapes were observed, which spread in  two subdistricts : Teluk Segara and Gading Cempaka Subdistricts.Each of cultural herritages and historic landscapesin Bengkulu City has different condition, so it required different treatment which includes : preservation, conservation, rehabilitation and reconstruction. Some objects are potential to be developed as historical tourism objects because of  their uniqness and high historical value, i.e: Fort Marlborough, Old Harbour, Tapak  paderi, Fatmawati house and Museum of Bengkulu. The potency of tourism sector also supported by the beautiful scenery and community which are cooperative and friendly.It is proposed that historical tourism objects in Bengkulu Province has devided in four clusters based on development potentiallity level and location of the objects. Cluster I as the maine development area, then followed by cluster II, III, and IV . Each cluster has main tourism object and supported by tourism facilities.